Empowering Junior High Learners: Improving English Proficiency through a Multidimensional Eclectic Strategy - Sophya, Ida Vera; Farida, Farida (Utamax : Journal of Ultimate Research and Trends in Education, 2025)
Improving English proficiency among junior high school students in Indonesia remains a pressing concern, especially when conventional methods seems fail to accommodate diverse learning needs. This study investigates the effectiveness of an eclectic teaching approach that combines cognitive, behavioristic, humanistic, and social strategies to enhance students’ English skills in reading, writing, listening, and speaking. The research responds to the lack of instructional methods that engage learners holistically and adaptively. A quasi-experimental design was employed involving 75 students at SMP N 2 Jati Kudus. Students were divided into an experimental group and a control group based on their pre-test scores. The experimental group, consisting of 28 students with scores below 60, received an eclectic intervention over eight weeks, while the control group of 47 students continued with conventional instruction. Data collection included pre-tests and post-tests, as well as questionnaires, interviews, and observations. Quantitative results showed a significant improvement in the experimental group, with the average post-test score rising to 74.48 from a pre-test mean of 61.06. The t-test yielded a value of 7.309 with p = 0.001, indicating a statistically significant difference. The experimental group showed a 38.31 percent increase in performance, with no decline among participants, compared to a 10.94 percent increase in the control group. The findings offer compelling evidence for integrating eclectic strategies in English language instruction and contribute to a growing body of research advocating for differentiated, holistic approaches in education.